Framing Palestine Celebgrams on Instagram Social Media Post The Events Of October 7 2023 - Yafuz, Labiq; Subaidi, Subaidi (Journal Of Middle East and Islamic Studies, 2024)
This research examines the framing conducted by Palestinian influencers on the social media platform Instagram following the Hamas attack on Israel on October 7, 2023. The study analyzes how these influencers use the platform to convey information about the conditions in Gaza after the attack. The methodology used is content analysis of several Palestinian influencers' accounts to observe differences in their content presentation. The findings indicate that the content uploaded by these influencers focuses on daily life, social impacts, and geographical conditions post-attack. This content aims to provide information and education to viewers about the current situation in Gaza. The framing by these influencers has successfully garnered international attention and prompted various forms of support, including donations